Generational Indigenation in a Multi-Ethnic and Religious Society (Tatarstan, Russia) - Aleksandrovna Maximova, Olga; Aleksandrovich Belyaev, Vladimir (Opción, 2018)
The authors researched ethnic and religious factors in order to detect the features of generational indigenation in multi-ethnic and -religious society of Tatarstan. The empirical data revealed the generational peculiarities of transferring the ethnic and religious values and the specifics of generational indigenation in Tatarstan. The conclusion is that the maintaining the ethnic and religious tolerance is possible both at society and in the sphere of intergenerational dynamics in this multiethnic and multi-religious region; the generational indigenation is limited. The authors revealed a number of specific generational characteristics that indicate the availability of certain generational shifts.